Penerapan Metode Tanya Jawab untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIMI Nawwarul Uyun NW 2 Tutuk - Mita Febriana; Maharani; Sirajun Nasihin (Pendidikan Al-Gafari, 2024)
Since education is a means of expressing the dynamic nature of human culture and a prerequisite for growth, any modifications or advancements in the field should be aligned with shifts in the culture of life. Study this aims to know the effective application method and ask for answers to increase results study student class VI at MI Nawwarul Uyun NW 2 Tutuk. Method ask answer chosen because can push interaction active between teacher and student as well as develop understanding student through question and focused answers on material learning. The research used is Study Action Class (PTK) with participants totaling 15 students from class VI MI Nawwarul Uyun NW 2 Tutuk. The study was done in two cycles, where every cycle consists of stage planning, implementation, observation, and reflection. Results study show a positive change in the interaction between teacher and student after applying the method to ask for answers more efficiently. The teacher is capable push participation and more students active by giving bait constructive feedback. Besides that mark, before the average applied method asks the answer is 63 under KKM 70, meanwhile after the applied method asks the answer with efficiency, the average value increases to 71 .4 on cycle first And reaches 77.6 in cycle second. Based on the observation of the results, can concluded that the application method asks for answers in a manner effective in learning Mathematics and can increase results study student class VI MI Nawwarul Uyun NW 2 Tutuk. Method this can push thinking critical and involve the student in learning.